Form for reporting Iowa Christmas bird counts to Iowa Bird Life, Peter C. Petersen, December 17, 1988 - Petersen, Peter C.et al (1988)
Iowa Christmas bird counts of species found in Muscatine contributed by Peter C. Petersen, December 17, 1988. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of winter 1988-1989. Epson - sheet feed